2010
DOI: 10.1007/s10584-010-9851-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of climate change impact on Eastern Washington agriculture

Abstract: A n assessment of the potential impact of climate change and the concurrent increase of atmospheric carbon dioxide (CO 2 ) concentration on eastern Washington State agriculture was conducted. Climate projections from four selected general circulation models (GCM) were chosen to evaluate impacts for the periods 2010-2039, 2030-2059 and 2070-2099, identified as 2020, 2040, and 2080 scenarios, respectively. All climate projections reflect a warming future climate, but the individual GCMs vary with respect to prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 49 publications
3
60
0
1
Order By: Relevance
“…In the Northwest, these false springs are projected to decline in frequency by the end of this century (Allstadt et al 2015, Peterson and. However, the spatially variable effects on spring onset and false springs may make local predictions of change difficult (Allstadt et al 2015), and minimum temperatures during early spring will still provide conditions for damaging frost events despite the warming trend (Stöckle et al 2010). Earlier and warmer springs will also pose challenges for pest management.…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Northwest, these false springs are projected to decline in frequency by the end of this century (Allstadt et al 2015, Peterson and. However, the spatially variable effects on spring onset and false springs may make local predictions of change difficult (Allstadt et al 2015), and minimum temperatures during early spring will still provide conditions for damaging frost events despite the warming trend (Stöckle et al 2010). Earlier and warmer springs will also pose challenges for pest management.…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Earlier and warmer springs will also pose challenges for pest management. For example, in the Northwest under some climate change scenarios, powdery mildew is projected to increase and codling moths may appear 4-14 days earlier and increase the fraction of third generation hatch (Stöckle et al 2010).…”
Section: Fruit Crop Vulnerabilities and Expected Changes In The Northmentioning
confidence: 99%
“…Compared to the historical baseline, the 50% probability total grain yield by the 2070s is projected to increase 23-37% for RCP 4.5 and 35-71% for RCP 8.5 depending on the AEC, with CC showing the greatest absolute increase and CF showing greatest relative increase compare to baseline yields. Based on limited studies in the IPNW, yields of wheatbased systems are projected to benefit from climate change for most of this century, with the degree of benefit depending on RCP (Thomson et al, 2002;Rosenzweig and Tubiello, 2007;Stöckle et al, 2010). Although, the yield response to future temperature changes can be fairly uncertain (Asseng et al, 2015), the moderate current temperatures in the region and earlier crop maturity under future conditions will mitigate deleterious effects of temperature on crop yields.…”
Section: Yields and Crop Water Usementioning
confidence: 99%
“…These projections remained unchanged when the variation of downloaded weather from 12 GCMs used in this study was considered or when yields with a probability of exceedance of 70% were used to classify AECs. One weakness of the study is the use of a single crop model for yield projections, although the CropSyst model has been used extensively in wheat studies in the IPNW (Pannkuk et al, 1998;Peralta and Stöckle, 2002;Stöckle et al, 2010; and around the world, Pala et al, 1996;Sommer et al, 2013;Donatelli et al, 2015;Holzkämper et al, 2015;O'Leary et al, 2015). Previous studies conducted with other models have also shown positive impacts of climate change in the region (Thomson et al, 2002;Rosenzweig and Tubiello, 2007).…”
Section: Aec Classification Based On Yield Percentilesmentioning
confidence: 99%
“…Extensive reports on climate change and adaptation sometimes include sections that specifically address agriculture. Australia has taken a close look at the community level to determine resilience and adaptability in food systems, employing its Extension Service in the effort (Boon, Millar, Lake, Cottress Cottrell, & King, 2012;Gero et al, 2013;Reid, 2011 Kruger, & Olen, in press;Kruger, Yorgey, & Stockle, 2011;Stockle et al, 2010). This is in response to the state's agricultural diversity, including the importance of high-value fruit and vegetable production to the economy, uncertainty of the agricultural water supply, the dependence on a winter moisture regime of the cereal-grain production region, and the relative vulnerability of the current regional agricultural system to global market dynamics.…”
Section: Impacts Of Climate Change and Adaptation Strategies: Productmentioning
confidence: 99%